1982
DOI: 10.1073/pnas.79.13.4153
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of active tolerance in maintenance of established islet of Langerhans allografts.

Abstract: Streptozotocin-induced diabetes in mice can be reversed by transplantation of islets of Langerhans from histoincompatible mice if the islets are treated with anti-Ia-serum and complement before transplantation. Here we show that anti-Iatreated islets most likely induce tolerance in the recipient animals. Daily injections of recipient-specific anti-I-J-serum (beginning 80 or more days after transplantation) and small numbers of donor splenocytes caused the prompt rejection of the islets in half of the animals; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Induction of established grafts. Rats with long-term (>60 days) islet or neoislet grafts were challenged with donor strain splenocytes to determine the mechanism of graft acceptance (13,14). Donor strain spleens (Lewis) were minced with scissors, and single-cell suspensions were obtained by pressing them through a fine nylon mesh and then treating them withTris-buffered ammonium chloride to lyse erythrocytes.…”
Section: Animalsmentioning
confidence: 99%
“…Induction of established grafts. Rats with long-term (>60 days) islet or neoislet grafts were challenged with donor strain splenocytes to determine the mechanism of graft acceptance (13,14). Donor strain spleens (Lewis) were minced with scissors, and single-cell suspensions were obtained by pressing them through a fine nylon mesh and then treating them withTris-buffered ammonium chloride to lyse erythrocytes.…”
Section: Animalsmentioning
confidence: 99%
“…In our early investigations on established islet allografts in rats, we had found some evidence of induction of specific tolerance in these animals [11]. In studies on mice that established islet allografts, following pretreatment of the islets with Ia antibody and complement, we found that repeated injections of anti-I-J antisera in conjunction with a single injection of only 10 4 donor spleen cells would induce rejection of established islet allografts in mice [12]. In control animals with established islet allografts of similar duration, >10 7 donor spleen cells were required to induce rejection.…”
Section: Effect Of Preimmunization Of Recipients With Ia-depleted Don...mentioning
confidence: 97%
“…Lymphocytes from "tolerant" animals respond normally to donor alloantigens in vitro [53,54]. More recently, Faustman et al [55] suggested that such unresponsiveness may be due to the action of suppressor cells; the role of suppressor cells in allograft tolerance has been reviewed elsewhere [56].…”
Section: Development Of Tolerancementioning
confidence: 99%